Hubungan Pengetahuan dan Sikap Ibu Terhadap Efek Samping Menstruasi Pada Pemakaian Alat Kontrasepsi KB Suntik 3 Bulan di PMB Hj. Zuniawati Tahun 2022 - Vivi Oktari (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
Family Planning is an attempt to extend of plan the number and distance of a pregnancy by using contraception. The purpose of this research is to find out if there is any knowledge and attitude to the three-month use of contraceptives. The design of the research is analytic survey by using cross sectional approach. Sample which taken is all mothers who come to use the three-month contraceptives in Hj. Zuniawati Apprentice Palembang which amount 32 people. According to the univariate analysis result obtained that from 32 respondents, who use the three-month contraceptives are 19 people (54,9%). According to the bivariate analysis result reached mothers with good knowledge use a three-month contraception group of 17 people (27.0%) are more than mothers with less knowledge who use a three-month contraception for 2 people (2.67%). According to bivariate analysis result obtained that Mothers who have positive attitude use three-month contraception namely 16 people (25.7%) are much more than mothers who have negative attitudeÂ Â use three-month contraception for 3 people (7.67%). From Bivariate analysis reached that there is a significant relation between knowledge with using three-month contraception (Ï value = 0,015), and reached that thereâ€™s not a significant correlation between attitude with using three-month contraception (Ï value = 0,109), advice to health workers especially midwives who work in Hj. Zuniawati Apprentice Palembang 2022 to promote good counseling as to contraception, it is an effective and efficient contraception.